Presentation and outcome of mixed neuroendocrine non-neuroendocrine neoplasms of the pancreas - Nießen, Anna; Schimmack, Simon; Weber, Tim; Mayer, Philipp; Bergmann, Frank; Hinz, Ulf; Büchler, Markus W.; Strobel, Oliver (Pancreatology, 2021)
Background/objectives - Mixed neuroendocrine non-neuroendocrine neoplasms (MiNEN) of the pancreas and periampullary region are extremely rare and heterogeneous malignancies. Literature is sparse, clinical management is not standardized and little is known about survival outcomes. The aim of this study was to identify pathological and radiological features of MiNEN and assess the outcome of surgical management. - Methods - Patients undergoing surgery for pancreatic and periampullary MiNEN between 2001 and 2019 were retrospectively analysed based on a prospective database. Histological, radiological and clinical features were assessed. Survival was analysed in a nested case-control study and matched-pair analyses with pure neuroendocrine neoplasms (pNEN) and ductal adeno- or acinar cell carcinomas of the pancreas. A literature review with focus on survival after surgical resection was additionally performed. - Results - Of 13 patients with MiNEN, 5 had acinar-MiNEN and 8 adeno-MiNEN. Two of 5 (40%) acinar-MiNEN and one adeno-MiNEN patients had liver metastases. All but one adeno-MiNEN (88%) showed preoperative radiological features of pancreatic adenocarcinoma, 3 of 5 (60%) acinar-MiNEN exhibited mainly neuroendocrine features. No surgical mortality was observed. The 5-year overall survival rate in all MiNEN was 40%. Five-year survival rate was 58% in adeno-MiNEN and comparable to that of matched ductal adenocarcinomas (36%) and pNEN (48%). Five-year overall survival rate was 20% in acinar-MiNEN, compared to 39% in acinar carcinoma patients and 59% in matched pNEN patients. - Conclusions - MiNEN are rare and difficult to distinguish from pure adenocarcinoma or neuroendocrine neoplasm preoperatively. Surgical resection would therefore be the treatment of choice in localized tumors.
Available online 3 December 2020
Gesehen am 15.12.2021